Implementation of Pesantren Accounting in the Preparation and Presentation of Financial Statements at SMP Pesantren Tarbiyah Takalar - Mira; Muryani Arsal; Nur Fadillah Safitri (Invoice : Jurnal Ilmu Akuntansi, 2025)
This study investigates the implementation of pesantren accounting in the financial reporting practices of SMP Pesantren Tarbiyah Takalar. Using a descriptive qualitative design, the research aims to provide a comprehensive understanding of how pesantren accounting principles are applied within an Islamic educational institution. Data were collected through interviews, observations, and document analysis, utilizing both primary and secondary sources to ensure the validity and reliability of findings. The analysis process involved data reduction, data presentation, and conclusion drawing using narrative techniques. The findings reveal that the school’s financial statements are not fully compliant with pesantren accounting standards and do not meet the requirements of ISAK 35, which governs financial reporting for nonprofit organizations, including Islamic boarding schools. Significant gaps were identified in the classification of assets, liabilities, and net assets, resulting in incomplete and less transparent reporting. These findings highlight the need for capacity building and training in financial management to improve compliance with standardized accounting frameworks. Strengthening the preparation and presentation of financial reports is crucial for enhancing transparency, accountability, and stakeholder trust. This research contributes to the literature on Islamic accounting by providing empirical evidence on the challenges faced by pesantren-based institutions in adopting standardized financial reporting practices, supporting efforts to improve financial governance and the sustainability of Islamic education.